2022
DOI: 10.20944/preprints202204.0130.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Exposure of Musculoskeletal Tissue to Extracorporeal Shock Waves

Abstract: Extracorporeal shock wave therapy (ESWT) is a safe and effective treatment option for various pathologies of the musculoskeletal system. Many studies addressed the molecular and cellular mechanisms of action of ESWT. However, no uniform concept could be established in this matter until now. We performed a systematic review of the effects of exposure of musculoskeletal tissue to extracorporeal shock waves (ESWs) reported in the literature. The key results were as follows: (i) compared to the effects of many oth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Specifically, results of animal experiments in vivo showed that ESWT could alleviate the infiltration extent of inflammatory cells, decrease the number and density of fibroblasts, improve collagen arrangement and reduce hypertrophic index of scars in a rabbit hypertrophic scar model 41,42 . Furthermore, experiments in vitro indicated that extracorporeal shock waves can regulate proliferation, migration and differentiation of keratinocytes and fibroblasts derived from scar tissue, reduce expression of transforming growth factor beta 1 (TGF‐β1), alpha smooth muscle actin (α‐SMA), collagen‐I, fibronectin and twist‐1, which might be responsible for the anti‐scarring effect of ESWT 43–46 . In Joo's study, mechanisms of ESWT were primarily attributed to a significant increase of micro‐perfusion in the PBPS area post ESWT 20 ; the latter can be achieved with both fESWT 47 and rESWT 48 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, results of animal experiments in vivo showed that ESWT could alleviate the infiltration extent of inflammatory cells, decrease the number and density of fibroblasts, improve collagen arrangement and reduce hypertrophic index of scars in a rabbit hypertrophic scar model 41,42 . Furthermore, experiments in vitro indicated that extracorporeal shock waves can regulate proliferation, migration and differentiation of keratinocytes and fibroblasts derived from scar tissue, reduce expression of transforming growth factor beta 1 (TGF‐β1), alpha smooth muscle actin (α‐SMA), collagen‐I, fibronectin and twist‐1, which might be responsible for the anti‐scarring effect of ESWT 43–46 . In Joo's study, mechanisms of ESWT were primarily attributed to a significant increase of micro‐perfusion in the PBPS area post ESWT 20 ; the latter can be achieved with both fESWT 47 and rESWT 48 …”
Section: Discussionmentioning
confidence: 99%
“…41,42 Furthermore, experiments in vitro indicated that extracorporeal shock waves can regulate proliferation, migration and differentiation of keratinocytes and fibroblasts derived from scar tissue, reduce expression of transforming growth factor beta 1 (TGF-β1), alpha smooth muscle actin (α-SMA), collagen-I, fibronectin and twist-1, which might be responsible for the antiscarring effect of ESWT. [43][44][45][46] In Joo's study, mechanisms of ESWT were primarily attributed to a significant increase of micro-perfusion in the PBPS area post ESWT 20 ; the latter can be achieved with both fESWT 47 and rESWT. 48 No serious adverse events after treating PBPS with ESWT + CRT were reported in the studies listed in Table 2.…”
Section: T a B L E 1 Study Design And Patient Characteristics Of Incl...mentioning
confidence: 99%
“…ESWT is a non-pharmacological and nonsurgical treatment modality for a variety of musculoskeletal disorders [12]. The molecular and cellular mechanisms of action of extracorporeal shock waves (ESWs) on musculoskeletal tissue were addressed in more than 180 studies in the literature [13]. A key mechanism is the reduction of pain sensation and a blockade of neurogenic inflammation through the overstimulation of substance P nerve fibers [14].…”
Section: Introductionmentioning
confidence: 99%